2001
DOI: 10.1128/iai.69.12.7839-7850.2001
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Functional Domains of the Mitogenic Toxin of Pasteurella multocida

Abstract: The locations of the catalytic and receptor-binding domains of the Pasteurella multocida toxin (PMT) were investigated. N-and C-terminal fragments of PMT were cloned and expressed as fusion proteins with affinity tags. Purified fusion proteins were assessed in suitable assays for catalytic activity and cell-binding ability. A C-terminal fragment (amino acids 681 to 1285) was catalytically active. When microinjected into quiescent Swiss 3T3 cells, it induced changes in cell morphology typical of toxin-treated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 56 publications
4
54
0
Order By: Relevance
“…3A). The substitution of Cys 1165 with serine, glycine, or arginine abolishes the PMT activities (15,17,18), which was confirmed in this study (Fig. 3B).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…3A). The substitution of Cys 1165 with serine, glycine, or arginine abolishes the PMT activities (15,17,18), which was confirmed in this study (Fig. 3B).…”
Section: Resultssupporting
confidence: 75%
“…Previous studies indicated that the intracellular toxic activity of PMT was attributable to its C terminus (15,17). To confirm this finding, we introduced the recombinant C-PMT (residues 569-1,285) directly into Swiss 3T3 cells with the aid of HVJ liposomes and examined the cells for elevated levels of DNA synthesis and PLC activity, which have usually been determined for the quantitative measurement of PMT toxicity (2,4,9).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is generally accepted that the toxin is structured according to a typical AB toxin. Initial studies revealed that the N terminus of PMT is involved in the binding and in translocation of the toxin into target cells (6), whereas the biologically active domain is located in the C-terminal part of the protein (6,7). This concept is in line with a significant sequence similarity of PMT at its N terminus with the N-terminal part of the cytotoxic necrotizing factor of Escherichia coli that is also involved in binding and translocation.…”
mentioning
confidence: 60%
“…multocida isolates can also be differentiated based on their ability to produce dermonecrotoxin (DNT). DNT exhibits osteolytic (DiGiacomo et al, 1993;Sternerkock et al, 1995) and mitogenic activity (Lax and Grigoriadis, 2001;Pullinger et al, 2001) which results into serious lesions (Chrisp and Foged, 1991;Schimmel et al, 1992). DNT was recorded mainly in isolates originating from pigs (Nielsen et al, 1986).…”
mentioning
confidence: 99%